Wet effluent diffusion denuder: The tool for determination of monoterpenes in forest - Křůmal, Kamil; Mikuška, Pavel; Večeřová, Kristýna; Urban, Otmar; Pallozzi, Emanuele; Večeřa, Zbyněk (Talanta, 2016)
Three methods, i.e., the cylindrical wet effluent diffusion denuder (CWEDD)-GCMS, Tenax tubes-GCMS and Proton-Transfer-Reaction Time-of-Flight Mass Spectrometry (PTR-TOF-MS) were compared for the determination of monoterpenes in forest. While the on-line technique (PTR-TOF-MS) allows only for the measurement of sum of monoterpenes, both the off-line preconcentration techniques (CWEDD and Tenax tubes) are suitable for the determination of concentrations of individual monoterpenes due to subsequent analysis of samples by GCMS. The CWEDD-GCMS is the only method that allows sampling of individual monoterpenes with short time intervals of 2-5min. Monoterpenes are absorbed into a liquid (n-heptane), flowing down on the inner wall of the CWEDD, and then the collected liquid with monoterpenes is immediately taken away for the GCMS analysis, which minimizes time when collected monoterpenes are exposed to oxidants presented in the air during sampling. The limits of detection of CWEDD-GCMS are in the range 1-7pptv for individual monoterpenes.
Keywords: heptany; monoterpeny; Tenax tubes; Monoterpene; Diffusion denuder; Heptanes; Mass Spectrometry; Forest; Proton-Transfer-Reaction Mass Spectrometry; Biogenic volatile organic compounds; lesy; hmotnostní spektrometrie; Monoterpenes; Forests